Role of Fungicide Applications on the Integrated Management of Wheat Stripe Rust - Carmona, Marcelo; Sautua, Francisco; Pérez-Hérnandez, Oscar; Reis, Erlei M. (Frontiers in Plant Science, 2020)
First described in Europe in 1777, stripe rust (SR) caused by Puccinia striiformis Westend. f. sp. tritici Eriks (Pst) is one of the most important and destructive diseases of wheat worldwide. Until 2000, SR was mainly endemic to cooler regions, but since then, new aggressive strains have emerged, spread intercontinentally, and caused severe epidemics in warmer regions across the world. This has put SR as a disease that poses a threat to the world food security. At present, the preferred strategy for control of SR is the access to wheat cultivars with adequate levels of SR resistance. However, wheat breeding programs are not sufficiently advanced to cope with the recently emerged Pts strains. Under this scenario, foliar fungicide applications have become an important component of SR management, but information on the effects of fungicide applications on SR control and wheat cultivar yield response is scarce. This review seeks to provide an overview of the impact and role of fungicides on SR management. With focus on wheat management in the major wheat-growing regions of the world, the review addresses: a) the efficacy of different fungicide active ingredients, optimal fungicide timing and number of applications in controlling SR, and b) the impact of fungicide on wheat grain yield response. Inclusion of fungicides in an integrated crop management approach is discussed.